On a question of Sadullaev concerning boundary relative extremal functions - Djire, Ibrahim K.; Wiegerinck, Jan (MATHEMATICA SCANDINAVICA, 2019)
We study the relation between certain alternative definitions of the boundary relative extremal function. For various domains we give an affirmative answer to the question of Sadullaev whether these extremal functions are equal.